The Narrative Legacy of Shajar al-Durr in Arabic Literature - Quinlan, Mary Evelyn (AUC Knowledge Fountain, 2026)
The story of the life of Shajar al-Durr (d. 1257) has been retold many times in Arabic literature in a variety of genres and mediums. In the pre-modern era, Shajar al-Durr’s biography appeared in the works of Ibn Wāṣil, Abū al-Fidāʾ, Al-Maqrīzī, and Ibn Taghrībirdī as well as the popular epic Sīrat Baybars. Many others have written about her since the 19th century, including Qadriyya Ḥusayn and Jurjī Zaydān. Writers of her biography used varying degrees of narrativization to create a story that served their needs, whether that was chronicling the history of 13th century Egypt or promoting contemporary ideological discourse. My research is a holistic and in-depth enumeration and analysis of the appearances of Shajar al-Durr’s life story in Arabic literature from the 13th century to the 21st.